The role of the Palestinian police in protecting victims of crimes - Taha, Musab Omar Al-Hassan; Almeshal, Wesam Mohammad (Journal of Economic, Administrative and Legal Sciences, 2021)
This paper aimed to identify the role of the Palestinian police in protecting the rights of victims by informing the victims of their rights, and determining the victim's right to protection by the judicial police. The researchers used the descriptive and analytical approach based on legal texts related to the protection of the rights of crime victims.This research paper concluded with a set of results and the important results are protection the human rights is the only way to make the human responsive about his community, and the balance between the individual rights and freedoms, the country right, community interest and it’s security and stability is vital necessity. The evidence of Palestinian police Confirmed the rights of victims in protection, and their right of recognizing their roles and the procedures that must be followed in their issues.At the end the two researchers recommended that police officers, especially judicial officers and the General Investigation Department, should receive adequate training to make them aware of how to deal with victims of crime. And how to define the victim's needs, know the principles of providing appropriate and immediate aid, establish rules for listening to the victim's complaint, deal with it and help her, and the need to notify the victim of interest in his case, and to inform him that his presence at the police headquarters will bring him justice and fairness.
Keywords: Palestinian police; crime victims; protection of crime victims